Digital Transformation in Entrepreneurial Ventures - Gorta, Tadej; Vukovič, Goran (Izboljševanje podjetniške izkušnje s pomočjo podpornega okolja v Ljubljanski urbani regiji, 2025)
This chapter examines the perceptions and experiences of digital transformation (DT) among employees at the Regional Development Agency of the Ljubljana Urban Region (RRA LUR). The aim of the research was to explore how employees understand and co-create digital changes, and to identify the key factors that either support or hinder this process. The study employed a quantitative method – an online survey enriched with elements of qualitative reflection, which enabled a deeper insight into individual perceptions. Results show that employees demonstrate an elevated level of readiness and motivation for DT, yet simultaneously perceive a lack of formal strategy, systemic support, and sufficient training. Key challenges include a gap between perceived confidence and actual knowledge, unclear leadership roles, and inconsistent communication. Based on the analysis, concrete recommendations are proposed at strategic, technical, and organizational levels. The conclusions emphasize the importance of an inclusive culture, leadership support, and the need for a more structured and sustainable approach to digital transformation.